Fabrication of multi-coal seam physical model and wavefield analysis of solid acquisition - Wang, Pan; Wang, Yunhong; Shi, Xianxin; Wang, Baoli; Liu, Qiang; Dong, Ruijing (Frontiers in Earth Science, 2025)
Quantitative detection of geological anomalies in coal mines is crucial for constructing transparent geological models and mitigating hidden disaster-causing factors. Aiming at the problem of quantitative detection of faults and goafs in underground coal mines, a multi-coal seam solid physical model including faults and goafs was designed and manufactured. The ultrasonic seismic physical simulation system was used to perform 2D solid data acquisition and migration imaging analysis of the model in direct contact with the transducer and the model. First, similarity material proportioning experiments for coal and rock were performed. After 33 groups of material ratio experiments, it was finally determined that the surrounding rock material was selected with epoxy resin and talcum powder with a mass ratio of 100:130, and the coal seam material was selected with epoxy resin and silicone rubber with a mass ratio of 100:60. The fabricated coal-rock specimens exhibited errors in Vp, Vs., and ρ all within ±5%. The 3D seismic physical models of multi-coal seams with dip angles of 45° and 90° and goafs were made by means of mold control horizon, anti-mold control structural accuracy, layer-by-layer pouring and 3D carving. Surface reflection acquisition was then performed for 2D wavefield analysis. The results show that the solid acquisition can obtain direct wave, surface wave, wave impedance interface reflection wave and interlayer multiple wave at the top and bottom interface of each coal seam. The rich wavefield responses confirm successful model fabrication, enabling quantitative analysis of anomaly characteristics.